2011
DOI: 10.1016/j.jneuroim.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Social disruption induced priming of CNS inflammatory response to Theiler's virus is dependent upon stress induced IL-6 release

Abstract: Chronic social disruption stress (SDR) exacerbates acute and chronic phase Theiler’s murine encephalomyelitis virus (TMEV) infection, a mouse model of multiple sclerosis. However, the precise mechanism by which this occurs remains unknown. The present study suggests SDR exacerbates TMEV disease course by priming virus-induced neuroinflammation. It was demonstrated that IL-1β mRNA expression increases following acute SDR; however, IL-6 mRNA expression, but not IL-1β, is upregulated in response to chronic SDR. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 90 publications
(146 reference statements)
3
14
0
Order By: Relevance
“…Both Th2 and Th17 responses have been linked with autoimmune disease susceptibility in animal models (Bettelli et al, 2007; Carding et al, 1993; Chen et al, 2006; Komiyama et al, 2006; Sutton et al, 2006; Ramsey et al, 1993; Rangachari et al, 2006) as well as impaired viral clearance (Hou et al, 2009). The current findings are consistent with the hypothesis that sensitization of the early proinflammatory cytokine response within the CNS translates into an impaired adaptive immune response (Vichaya et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Both Th2 and Th17 responses have been linked with autoimmune disease susceptibility in animal models (Bettelli et al, 2007; Carding et al, 1993; Chen et al, 2006; Komiyama et al, 2006; Sutton et al, 2006; Ramsey et al, 1993; Rangachari et al, 2006) as well as impaired viral clearance (Hou et al, 2009). The current findings are consistent with the hypothesis that sensitization of the early proinflammatory cytokine response within the CNS translates into an impaired adaptive immune response (Vichaya et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…Social stress has previously been shown to stimulate and/or sensitize the innate proinflammatory cytokine response (Meagher et al, 2007; Quan et al, 2001; Vichaya et al, 2011). In the TMEV model specifically, we have found that SDR alone increases circulating and CNS levels of the pro-inflammatory cytokine IL-6 and blocking IL-6 activity during SDR exposure attenuates the exacerbation of the acute TMEV disease (Meagher et al, 2007; Vichaya et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LCMV is a systemic infection with a very different tissue tropism and infectious course than IAV, which makes it difficult to directly compare the effect of SDR on immune parameters in each viral system. In a mouse model of a neurotropic virus infection, Theiler’s murine encephalomyelitis virus, SDR prior to infection exacaberated disease by priming virus-induced neuroinflammation, however, the experience of the social stressor during infection had beneficial effects on clinical disease course and inflammation (Johnson et al, 2004; Vichaya et al, 2011). These differences underscore the importance of both the timing of the stressor and the cellular infectious profile of the viral agent used when comparing neuroendocrine regulation of replicating antigens.…”
Section: Discussionmentioning
confidence: 99%